Pengaruh Endorphin Massage terhadap Nyeri Haid Mahasiswi Tingkat Akhir S1 Keperawatan Universitas Nahdlatul Ulama Surabaya - Yurike Septianingrum; Nety Mawarda Hatmanti (Jurnal Keperawatan Muhammadiyah, 2019)
Introduction: Menstrual pain or dysmenorrhea is a common problem that is often complained of by women during menstruation. Menstrual pain can interfere learning activities, especially final year students in completing their thesis. The purpose of this study were to analyze the effect of endorphin massage on menstrual pain in final year nursing students of UNUSA. Method: This study using an experimental with pre-test and post-test control group design. Research subjects of this study was recruited using simple random sampling who was included inclusion and exclusion criteria. Research subjects in this study was of 46 students who were then divided into two groups, 23 students into intervention group and 23 students into control group. Data were collected by using observation with VAS. Data were analyzed by using Wilcoxon and Mann-Whitney U test. Result and Analysis: The results showed that: 1) There was difference VAS score between pre test and post test in intervention group (p= 0,000), 2) There was difference VAS score between intervention and control group (p= 0,017). Conclusion: Endorphin massage could reduce menstrual pain in final year nursing student of UNUSA. Further research, is expected that endorphin massage can be compared with music therapy to reduce menstrual painKeywords: endorphin massage, menstrual pain, primary dysmenorrhea